The PI3K/AKT Pathway and Renal Cell Carcinoma. Issue 7 (20th July 2015) - Guo, Huifang; German, Peter; Bai, Shanshan; Barnes, Sean; Guo, Wei; Qi, Xiangjie; Lou, Hongxiang; Liang, Jiyong; Jonasch, Eric; Mills, Gordon B.; Ding, Zhiyong
Abstract The phosphatidylinositol 3 kinase (PI3K)/AKT pathway is genetically targeted in more pathway components and in more tumor types than any other growth factor signaling pathway, and thus is frequently activated as a cancer driver. More importantly, the PI3K/AKT pathway is composed of multiple bifurcating and converging kinase cascades, providing many potential targets for cancer therapy. Renal cell carcinoma (RCC) is a high-risk and high-mortality cancer that is notoriously resistant to traditional chemotherapies or radiotherapies. The PI3K/AKT pathway is modestly mutated but highly activated in RCC, representing a promising drug target. Indeed, PI3K pathway inhibitors of the rapalog family are approved for use in RCC. Recent large-scale integrated analyses of a large number of patients have provided a molecular basis for RCC, reiterating the critical role of the PI3K/AKT pathway in this cancer. In this review, we summarize the genetic alterations of the PI3K/AKT pathway in RCC as indicated in the latest large-scale genome sequencing data, as well as treatments for RCC that target the aberrant activated PI3K/AKT pathway.